GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 120225 species occurrences available in GBIF matching the query: TaxonKey: Echinoidea HasCoordinate: true HasGeospatialIssue: false. The dataset includes 120225 records from 252 constituent datasets: 740 records from BioMar - LIFE project. 30 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 102 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 223 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 28 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 950 records from Marine species distributions in Irish coastal waters. 258 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 6 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 9 records from Zoology (Museum of Evolution - Uppsala). 571 records from TCWC Marine Invertebrates. 14 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 100 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 5 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 130 records from Biological Reference Collections ICM CSIC. 1075 records from NPL collections. 14 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 31 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 48 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 2929 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 45 records from BioFokus. 521 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 83 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 15 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 112 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 2 records from Counts of benthos communities in Kongsfjorden in 2009. 4249 records from Artdata. 1103 records from Museum Victoria provider for OZCAM. 1671 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 5381 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 20 records from Lund Museum of Zoology (MZLU). 6 records from kyklades. 38 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 2493 records from CAS Invertebrate Zoology (IZ). 3 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 240 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 44 records from Colección de Zoología Invertebrados - Otros invertebrados. 25 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 153 records from Norwegian Biodiversity Information Centre - Other datasets. 727 records from Museum of Comparative Zoology, Harvard University. 1 records from Australia's Virtual Herbarium. 826 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 845 records from iNaturalist Research-grade Observations. 112 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 1 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 187 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 1 records from Recent Invertebrates Specimens. 547 records from Invertebrates Collection of the Swedish Museum of Natural History. 13 records from Estonian Museum of Natural History. 26 records from University of California Museum of Paleontology. 10 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 12490 records from NMNH occurrence DwC-A. 105 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Wangerooge. 130 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 34 records from CSIRO, Marine Data Warehouse Biology Records Pre-1998, Australia, 1978-1997. 4196 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 47 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 8 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 103 records from Diveboard - Scuba diving citizen science observations. 21 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 39 records from naturgucker. 74 records from CSIRO, Cruise SS200702, Marine Biodiversity Survey, Southeast Australia, 2007. 655 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 38 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 230 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 9 records from The near-bottom plankton and benthic invertebrate fauna of Josephine and Great Meteor Seamounts (Table 2). 98 records from Natural England - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 119 records from Benthos counted on dredged samples during Valdivia cruise VA44. 129 records from Benthos counted on dredged samples during Valdivia cruise VA53. 9 records from Benthos abundance in surface sediment sampled during cruise ANT-V/1. 37 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 21 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 14 records from MfN - Fossil invertebrates Ia. 88 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 104 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 16 records from Rådgivende Biologer. 2 records from Macrofauna biomass in surface sediment sampled during cruise DI222/2. 3 records from Macrofauna biomass in surface sediment sampled during cruise DI226. 2 records from Macrofauna biomass in surface sediment sampled during cruise DI229. 1 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 2 records from Macrofauna biomass in surface sediment sampled during cruise DI237. 336 records from Northern Territory Museum and Art Gallery provider for OZCAM. 115 records from (Table T2) Biogenic and mineral composition of sediments cored in Vaale, Schleswig-Holstein. 2047 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 25 records from MNA - Sezione di Genova - (Marine Biological Samples). 2 records from Antarctic Marine Species Sequence Data. 14 records from South American Antarctic Marine Biodiversity Literature. 118 records from Collection Echinodermata - ZMB. 68 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 72 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE278. 84 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE293. 93 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 87 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE241. 315 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE255. 229 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE258. 154 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE262. 203 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE272. 133 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE206. 46 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE218. 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 1 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 2 records from (Table 2) Median abundances of macrobenthos in surface sediments. 3 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD3. 142 records from Texture description and distribution of components in ODP Hole 103-639D (Figure 2). 205 records from Natural History Museum (London) Collection Specimens. 3 records from Macaulay Library Audio and Video Collection. 4 records from Sistematización de la Colección Paleontológica de la Facultad de Ingeniería, UNAM. 44 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 2 records from Diversidad bentónica del ambiente intermareal e infralitoral somero de Progreso, Yucatán. 6 records from Ireland's BioBlitz. 97 records from Biodiversidad de la macrofauna bentónica en la microcuenca de Chabihau, Yucatán. 4 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 1 records from Distribución e inventario de algunas especies bentónicas (hexacorales, octocorales, esponjas, y especies misceláneas) en arrecifes del Caribe mexicano. 181 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 46 records from Inventario de la biota marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 128 records from UAM Invertebrate Collection (Arctos). 19 records from Akita Prefectural Museum＋Echinoderms Specimens of Akita Prefectural Museum. 59 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 57 records from IG TUT paleontology. 40 records from Tartu University, palaeontology collections. 71 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 826 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Benthos monitoring of the North Sea_ research database. 6 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 281 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during HEINCKE cruise HE133. 60 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 157 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 36 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 198 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Tridens00/5. 135 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 43 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 15 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 49 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 8 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 10 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 12 records from (Table 1) Occurrence of bottom invertebrates in the Canary upwelling area. 1 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 23 records from SOMBASE. 311 records from EPA'S EMAP Database. 279 records from NODC WOD01 Plankton Database. 542 records from SeamountsOnline (seamount biota) (CoML). 56 records from The SERTC Invertebrate Database: Invertebrates of the southeastern United States. 435 records from Natural Geography In Shore Areas (NaGISA) Dataset. 233 records from NBI. 2243 records from North Pacific Groundfish Observer (North Pacific Research Board). 64 records from Bishop Museum Data (OBIS distribution) (USOBIS). 60 records from Atlantic Reference Centre (OBIS Canada). 4 records from Bay of Fundy Species List (OBIS Canada). 863 records from ``South Western Pacific Regional OBIS Data provider for the NIWA Marine Biodata Information System``. 4 records from ChEssBase (CoML). 120 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 4 records from Benthic fauna in the Pechora Sea (EurOBIS). 101 records from MedOBIS (EurOBIS). 3 records from BioMar (EurOBIS). 45 records from Biogeography Scheldt Estuary (EurOBIS). 359 records from Macrobel: Long term trends in the macrobenthos of the Belgian Continental Shelf (EurOBIS). 28 records from A comparison of benthic biodiversity in the North Sea, English Channel and Celtic Seas (EurOBIS). 396 records from Gwaii Haanas Invertebrates (OBIS Canada). 26 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 34 records from SINBIOTA - marine data (OBIS South America, BRAZIL). 272 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Macrofauna. 99 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Trawl. 14 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 8 records from Cross Sands broadscale survey 1998 (EurOBIS). 104 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 345 records from Histroical benthic dredge samples from the southern baltic and the North Sea (EurOBIS). 95 records from Posidonia Oceanica Survey 2005 (EurOBIS). 82 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 1 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 2 records from Marine and Coastal Management - Demersal Surveys (years 1996-2000) (AfrOBIS). 45 records from Marine and Coastal Management - Demersal Surveys (years 2001-2005) (AfrOBIS). 69 records from Marine and Coastal Management - Demersal Surveys (years 2006-) (AfrOBIS). 6369 records from Paleobiology Database. 46 records from Arctic Ocean Diversity. 1 records from Galathea II, Danish Deep Sea Expedition 1950-52. 12 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 1701 records from Invertebrate Paleontology Division, Yale Peabody Museum. 395 records from Invertebrate Zoology Division, Yale Peabody Museum. 115 records from IndOBIS, Indian Ocean Node of OBIS. 2204 records from invertebratezoology. 35 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 1334 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 774 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 5 records from NCOS1959_Crustacea (OBIS China). 1326 records from NCOS1959_Echinodermata (OBIS China). 4 records from MAL. 31 records from AAD Benthic Sampling Database. 1074 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 1202 records from Antarctic Echinoids: an interactive database. 4 records from Artenvielfalt der Nordsee - Helgoland. 4 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 4 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 1 records from Artenvielfalt der Nordsee - Sylt. 11 records from Isle of Wight Local Records Centre - IOW Natural History & Archaeological Society Marine Invertebrate Records 1853- 2011. 101 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 22 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 2 records from Scuba Diving Observations. 211 records from Sponges of Rathlin Island. 5 records from ELM paleontology. 957 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1202 records from Biodiversity of Antarctic Zoobenthos (SCAR-MarBIN: Antarctic OBIS). 313 records from Biological and palaeontological collection and observation data MNHNL. 378 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 83 records from COMARGIS: Information System on Continental Margin Ecosystems. 2598 records from KU Museum of Invertebrate Paleontology. 199 records from Collection Echinodermata SMF. 13 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 24 records from Benthic macrofauna abundance and biomass in surface sediment during cruise CD86. 2 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG93. 5 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG95A. 617 records from hauterivian_echinoids_of_the_paris_basin. 7153 records from University of Florida Invertebrate Paleontology. 312 records from imr_mareano_beamtrawl. 5 records from UAM Earth Sciences Collection (Arctos). 724 records from Queensland Museum provider for OZCAM. 16 records from Bureau of Rural Sciences, Commercial Fisheries Presence, Australia, 2000-2002. 2 records from Lund Botanical Museum (LD). 647 records from Geographically tagged INSDC sequences. 33 records from Norwegian Species Observation Service. 5864 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 26 records from (Table 2) Sediment constituents and quartz in the sand-sized fraction, West Florida slope and Eastern Mississippi Fan, during USGS R/V Gyre cruises G80-6A and G81-8. 2482 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 132 records from NORFANZ Biological Survey, Tasman Sea, Australia - New Zealand 2003. 2 records from Wildlife Sightings. 68 records from Bernice P. Bishop Museum. 2 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 2 records from (Table 2) Megafauna density 2002, 2004 and 2007 in the deep-sea observatory AWI-HAUSGARTEN, Fram Strait. 66 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar1. 7 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar3. 1 records from Succession of benthic hard-bottom communities abundance at station Errina2012_AG. 10 records from CU Invertebrate Paleontology. 25 records from European Molecular Biology Laboratory Australian Mirror. 12 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 3 records from Highland Biological Recording Group - HBRG Other Invertebrates Dataset. 71 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 2274 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN.. 7379 records from Marine Conservation Society - Seasearch Marine Surveys. 68 records from Queen Victoria Museum Art Gallery provider for OZCAM. 20 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 249 records from imr_mareano_grab. 4 records from NCSM Invertebrates Collection. 1107 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 5171 records from Australian Museum provider for OZCAM. 62 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 1781 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 19 records from Occurrences in SinBIOTA. 27 records from imr_mareano_rpsledge. 1 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 30 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 1 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 330 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 39 records from National Museum of Natural Science.
Keywords: GBIF; biodiversity; species occurrences